2015
DOI: 10.1083/jcb.201504044
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of solid RNP granules control normal RNP dynamics and mRNA activity in early development

Abstract: Modifiers of aberrant solid RNP granules suggest new insights into pathways that control dynamics of large-scale RNP bodies and mRNAs during C. elegans oogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 86 publications
(179 reference statements)
1
38
0
Order By: Relevance
“…It is possible that the RNA species in the normal, mature axons are translationally repressed until they are activated by the injury. Adaxonal glia may play an important role in this activation of the intrinsic translational machinery in the axon in addition to supplying functional ribosomes.There is ample evidence for such a regulatory mechanism in nature, e.g, in the oocyte where mRNAs are packaged with ribonucleoprotein particles (RNPs) and are translationally repressed by multiple mechanisms until they are activated in later stages of oogenesis (Hubstenberger et al 2015). Many other examples exist in which mRNA binding proteins (RBPs) store mRNAs in inactive forms until regulatory mechanisms are invoked to activate translation (Anderson and Kedersha 2008;Kiebler and Bassell 2006;Thomas et al 2011;Wells 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the RNA species in the normal, mature axons are translationally repressed until they are activated by the injury. Adaxonal glia may play an important role in this activation of the intrinsic translational machinery in the axon in addition to supplying functional ribosomes.There is ample evidence for such a regulatory mechanism in nature, e.g, in the oocyte where mRNAs are packaged with ribonucleoprotein particles (RNPs) and are translationally repressed by multiple mechanisms until they are activated in later stages of oogenesis (Hubstenberger et al 2015). Many other examples exist in which mRNA binding proteins (RBPs) store mRNAs in inactive forms until regulatory mechanisms are invoked to activate translation (Anderson and Kedersha 2008;Kiebler and Bassell 2006;Thomas et al 2011;Wells 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, VCP, which is associated with both ALS and multisystem proteinopathy (Johnson et al, 2010; Watts et al, 2004), is critical to both RNP granule disassembly and pathological aggregate clearance (Buchan et al, 2013; Ju et al, 2009; Meyer and Weihl, 2014). Moreover, RNA helicases such as Ddx6 may be critical to maintaining fluidity of these compartments, preventing the formation of pathological solids (Hubstenberger et al, 2015; 2013). …”
Section: Liquid-to-solid Phase Transitions In Disease Pathogenesismentioning
confidence: 99%
“…Y2H data indicated that B0035.6 interacts with DEPS-1 via its C-terminal region ( Figure S3A). B0035.6 has no predicted conserved domain structures but a low similarity to human MEG-3 (Hubstenberger et al, 2015). B0035.6 was also one of the significant interactors of PRG-1 in our proteomic analysis (Table S1, Figure S3B), suggesting DEPS-1, B0035.6 and PRG-1 form a trimeric complex.…”
Section: Edg-1 Interacts With Both Deps-1 and Prg-1 And Modulates Depmentioning
confidence: 91%